Comparative phylogeography of the catshark, Haploblepharus pictus and its nematode parasite, Proleptus obtusus - McLachlan, Ann (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc (Botany and Zoology))--Stellenbosch University, 2011.